2017
DOI: 10.1177/0010414016688002
|View full text |Cite
|
Sign up to set email alerts
|

Poor People’s Participation: Neoliberal Institutions or Left Turn?

Abstract: While comparative political studies of voting and protest abound, little attention has been paid to nonelectoral and noncontentious participation, particularly at the local level. Who participates in local associations and why? We study the individual-level determinants of local civic participation in Bolivia to ask: Does local engagement reproduce the high socioeconomic bias predicted by resource theory? Did the left turn in government change the predictors of participation? Contrary to expectations, we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…As mentioned previously, Gunnarsson et al (2009) found that there was greater participation in SBM among rural communities in Latin America. More generally, Davies and Falleti (2017) noted that low-income, indigenous and rural groups in Bolivia are more likely to participate in local community associations, while Krishna (2006) found that the propensity to participate in rural local government in India is uncorrelated with wealth or caste grouping.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, Gunnarsson et al (2009) found that there was greater participation in SBM among rural communities in Latin America. More generally, Davies and Falleti (2017) noted that low-income, indigenous and rural groups in Bolivia are more likely to participate in local community associations, while Krishna (2006) found that the propensity to participate in rural local government in India is uncorrelated with wealth or caste grouping.…”
Section: Discussionmentioning
confidence: 99%
“…El Alto has thousands of active civil society groups (Arbona and Kohl 2004;Copa Pabón 2020;Tassi et al 2015), and Bolivia writ large has a highly organized civil society (Boulding 2014). Most adults and many children participate in at least one civil society organization, and the groups are organized locally into associations or unions, then into municipal federations, and then into larger peak organizations or confederations (Anria 2018;Davies and Falleti 2017).…”
Section: Assumptionsmentioning
confidence: 99%
“…Officials in cash-strapped municipalities like El Alto or Tucumán, Argentina delegate many of these tasks to civil society groups to fill in goods and services where the state falls short (Amengual 2016;Auerbach 2019;Bodea and LeBas 2016). These organizations have dense webs of working relationships and agreements with local officials (Davies and Falleti 2017;Derpic 2019;Hummel 2016). The agreements help both officials and civil society leaders get their work done in cities with tiny budgets, new and weak institutions, and unreliable information (Auyero 2001;Goldstein 2016;Helmke and Levitsky 2004).…”
mentioning
confidence: 99%
“…Depending on a specific society's salient cleavages, these societal organizations can take various forms: whereas some of these organizations might be characterized as primarily classist (e.g., informal sector unions, employer associations, and labor unions), others are primarily ethnic (e.g., indigenous organizations). Yet others span across these divides (e.g., the cocaleros in Bolivia) or take the form of "local programmatic associations" (e.g., neighborhood associations) (Davies and Falleti 2017, 1700-1701. Regardless of the interests at their core, such organizations can "provide a mechanism through which citizens who have a shared attitude or a shared interest can come together and channel their collective resources into political action" (Thomas 2001, 7).…”
Section: Societal Organizationsmentioning
confidence: 99%
“…Irrespective of the underlying interests, these organizations are relatively long-lived and exhibit stable membership. Their existence predates the electoral success of the MAS and membership/participation in them, and the socioeconomic composition of their membership has been unaffected by the country's left turn (Davies and Falleti 2017).…”
Section: The Role Of Societal Organizations In Boliviamentioning
confidence: 99%